Sex discrimination - Merino, Noel. (Farmington Hills, MI : Greenhaven Press, 2010)
Presents articles regarding sex discrimination in the United States, including cases relating to military benefits, divorce settlements, affirmative action for women, and sex discrmination in the workplace.
Sex discrimination in military benefits -- Case overview: Frontiero v. Richardson (1973). The court's decision: differential treatment of men and women is unconstitutional / William J. Brennan Jr. -- The statute in question treating men and women differently is reasonable / Erwin N. Griswold, Harlington Wood Jr., Mark L. Evans -- The decision in Frontiero was a key step toward equality for women / Christine Basic -- The Frontiero decision helped women achieve equality in the military / Lory Manning -- The reasoning in Frontiero protecting women supports protection of homosexuals / Thomas B. Scheffey -- Striking down statutes requiring alimony only of men -- Case overview: Orr v. Orr (1979). The court's decision: legislation distributing benefits and burdens by gender is unconstitutional / William J. Brennan Jr. -- Dissenting opinion: no sex discrimination exists for an individual who is not harmed / William H. Rehnquist -- Men receiving alimony still suffer stigmatization years after Orr / Anita Raghavan -- Women are increasingly paying alimony as equality requires / Betsy Schiffman -- Upholding affirmative action for working women -- Case overview: Johnson v. Transportation Agency (1987). The court's decision: taking account of sex in order to eliminate underrepresentation in employment is constitutional / William J. Brennan Jr. -- Dissenting opinion: in employment, taking sex into account for any reason is sex discrimination / Antonin Scalia -- Brennanism / Daniel Seligman -- The relevance of Johnson for ad hoc affirmative action is unclear / Michael Starr and Adam J. Heft -- Validating limits on suing employers for sex discrimination -- Case overview: Ledbetter v. Goodyear Tire & Rubber Co. (2007). The court's decision: filing for pay discrimination is subject to time limits / Samuel A. Alito Jr. -- Dissenting opinion: current pay disparities between men and women are acts of sex discrimination / Ruth Bader Ginsburg -- Ledbetter was not unjustly decided / Stuart Taylor Jr. -- Congress should overturn Ledbetter / Dahlia Lithwick -- The Lilly Ledbetter Fair Pay Act will create many problems / Andrew M. Grossman.
Includes bibliographical references and index.
Keywords: Sex discrimination -- Law and legislation -- United States -- Cases -- Juvenile literature